Programa de educación nutricional, con abordaje multidisciplinario, para desarrollar la cultura alimentaria en estudiantes de educación secundaria- Huamachuco, 2017 - Rabanal Gutiérrez, Jessica Jacqueline (2019)
ABSTRACT The objective of this study was to determine the level of food culture in high school students of Huamachuco, through the nutritional education program, with a multidisciplinary approach. The population was constituted by 150 students and the sample of 30 students of the 1st Secondary. The design used was pre-experimental with one group with application of Pre and Post test. It was determined that the nutritional education program "healthy foods", with multidisciplinary approach, significantly develops the food culture in high school students-Huamachuco, 2017.